Implications of the Polish 1999 Administrative Reform for Regional Socio-Economic Development - Michal Myck; Mateusz Najsztub (Institute of Labor Economics (IZA), 2019)
On 1 January 1999, four major reforms took effect in Poland in the areas of health, education, pensions and local administration. After 20 years, only in the last case does the original structural design remain essentially unchanged. We examine the implications of this reform from the perspective of the distance of municipalities from their regional administrative capital. We show that despite fears of negative consequences for peripheral regions, the reform did not result in slower socio-economic development for those municipalities that found themselves further from the new administrative centres. We argue that regional inclusiveness in the process of development is likely to be an important factor behind the stability of Poland's administrative design.
Keywords: P30; R11; R50; 330; regional development; administrative reform; distance to capitals; differences in differences